Source and characteristics of blue, infrared (IR), and post-IR IR stimulated signals from gypsum-rich samples - Clark-Balzan, Laine (Ancient TL, 2016)
Samples collected from gypsiferous deposits in the Nefud Desert, Saudi Arabia, yielded anomalous signals when presumed quartz and feldspar extracts were measured with BSL and pIRIR290 SAR protocols, respectively. Subsequent scanning electron microscopy analysis indicated that the majority of extracted coarse grains were gypsum instead of quartz or feldspar. Luminescence signals were detected from gypsum at room or low (50 ◦C) temperature when stimulated with blue (UV detection: 330, 380 nm) or IR (blue detection) light. No UV (330 nm) emissions were detected with IRSL stimulation. A modified SAR protocol (no preheats) was successful in building saturating exponential growth curves for BSL/UV380 and IRSL/blue emissions from gypsum, with acceptable recycling and zero ratios. Luminescence measurement of gypsum with standard protocols used for quartz (BSL/UV340 SAR with preheats) and feldspar (pIRIR290 with preheats) yielded either negligible or anomalous signals that could be excluded from consideration via typical rejection criteria. Additionally, massive decrease in sensitivity with SAR cycle was found to be indicative of gypsiferous content. Therefore measurement of quartz and feldspar aliquots according to standard procedures should be possible even in gypsum-contaminated samples, though concentration of these minerals via an extra density separation step may be necessary.